2015
DOI: 10.1371/journal.pone.0127578
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Prevalence and Associated Risk Factors of Tinnitus in Adults

Abstract: BackgroundTinnitus is a common condition in adults; however, the pathophysiology of tinnitus remains unclear, and no large population-based study has assessed the associated risk factors. The aim of this study was to analyze the prevalence and associated risk factors of tinnitus.MethodsWe conducted a cross-sectional study using data from the Korea National Health and Nutrition Examination Survey, with 19,290 participants ranging in age from 20 to 98 years old, between 2009 and 2012. We investigated the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
219
4
39

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(297 citation statements)
references
References 44 publications
(82 reference statements)
15
219
4
39
Order By: Relevance
“…Tinnitus is a common condition, especially in cancer treatment, caused by chemotherapy drugs and radiotherapy [17,[20][21][22]. The present study did not reveal relation between tinnitus and hearing loss, in contrast investigators have reported this relation [20].…”
Section: Discussioncontrasting
confidence: 89%
“…Tinnitus is a common condition, especially in cancer treatment, caused by chemotherapy drugs and radiotherapy [17,[20][21][22]. The present study did not reveal relation between tinnitus and hearing loss, in contrast investigators have reported this relation [20].…”
Section: Discussioncontrasting
confidence: 89%
“…The prevalence tends to increase from 4-6% in young adults to 10-20% in those aged 70-79 years [Axelsson and Ringdahl, 1989;Ries, 1994;Davis and MRC Institute of Hearing Research, 1995;Shargorodsky et al, 2010;Fabijańska et al, 2012;McCormack et al, 2014;Kim et al, 2015;Martinez et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Tinnitus is known to cause disruption of sleep patterns 3 and more tinnitus in people reporting little sleep (< 6 hours) has been reported 32 . We found no significant differences in reported sleep quality between musicians with and without tinnitus, but sleep disturbance positively predicted the degree of tinnitus-affection and concern (table 2).…”
mentioning
confidence: 99%